PENELUSURAN KARAKTERISTIK PERILAKU KONSUMEN DENGAN METODE AUTOMATIC INTERACTION DETECTION (AID) - Rusgiyono, Agus (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2008)
AID methods used to see relation between respons variable with a number of variable of predictor and also see related pattern between predictors. In AID procedures data disjointed in two group determined by variable of predictor most explaining of difference values of respons variables, and this recuring process so that yielded to with refer to splits in data. Every split yield new data sub which its variable values is mutually and exclusive exhaustive. Its end results with refer toing crotch is so-called tree of AID Keywords : split, tree of AID